Interest Groups in the Decision-Making Process in Chile, 1990-2020. Who, Where and How Much; [Los Grupos de Interés en el Proceso de Toma Decisiones en Chile, 1990-2020. ¿Quién, Dónde y Cuánto] - Segovia-Arancibia, C (Ibero-Amerikanisches Institut Preußischer Kulturbesitz, 2024)
[No abstract available]